Uma "pretensa intentona": ANL, AIB e a cultura política anticomunista no Estado do Amazonas (1935-1937) - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
The 1930s highlighted fierce world political disputes, such as the rise of nazism in Germany, the organizations of the popular fronts, the consolidation of the Union of Soviet Socialist Republics (USSR), the outbreak of World War II. At the national level, the disputes that began in the 1920s - against the political game of the First Republic - flowed into the “1930 revolution” and the establishment of the Provisional Government, with Getúlio Dorneles Vargas ahead. It was in the midst of these disputed that new characters emerged in the Brazilian political scene. On the one hand, came the Brazilian Integralist Action (BIA), articulated by Plínio Salgado under the strong influence of italian fascism. On the other hand, the National Liberation Alliance (NLA) emerged, gathering around itself people from various social classes who put the fight against fascism, landlordism and imperialism on the agenda. Both entities were present in the Amazonas political scene, being inaugurated between 1934- 1935, disputing minds and hearts. However, NLA it was outlawed, and its remaining members - communists and tenentists - prepared a uprising against the Vargas government. In November 1935, a rebellion broke out in Natal that would soon spread to other Brazilian cities, especially Rio de Janeiro and Recife - this event was known in historiography as “Communist uprising of 1935”. In addition to these cities that carried out the uprising, a plan was devised to overthrow the Amazonas governor, Álvaro Maia, but the plan was not implemented. During the days of the uprising, the actions of the rebels spawned a range of discourses, representations, and imaginations repeated and crystallized to this day. The objective of this research is to contribute historiographically to the understanding of political history in the state of Amazonas from the analysis of the levantes of november 1935 and in this motto: 1. To present the scene of the politician of Amazonas in the 1930s, highlighting the elections of 1933, 1934 and 1935 and agents involved in political disputes at national and local level; 2. Investigate the emergence of the core of Brazilian Integralist Action (BIA) and the National Liberation Alliance (NLA) in the Amazonas; 3. Highlight the uprisings in Rio Grande do Norte, Pernambuco, Rio de Janeiro and, finally, the attempted armed uprising in the state of Amazonas; 4. Analyze the anti-communist representations (action and imaginary) conveyed in the press of the state of Amazonas. In order to achieve these objectives, a coherent and efficient theoretical-methodological approach is required. In this sense, this work seeks to join the field of New Political History, using periodicals and criminal proceedings, as such sources are of paramount importance for those who research the popular strata of society, as it is usually where they appear, most often when they commit offenses or are charged with one.
Keywords: Revolução de 1930; Anticomunismo; Aliança Nacional Libertadora; Intentona Comunista; Comunismo - Amazonas; CIÊNCIAS HUMANAS: HISTÓRIA; ANL; Levantes de Novembro de 1935; Anticomunismo